2021
DOI: 10.1016/j.earlhumdev.2021.105483
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on developmental care practices for infants born preterm

Abstract: Objectives To assess the impact of the COVID-19 pandemic on rates of hospital visitation and rates and durations of developmental care practices for infants born preterm. Methods We analyzed electronic medical record data from 129 infants born at less than 32 weeks gestational age (GA) cared for in the Lucile Packard Children’s Hospital neonatal intensive care unit (NICU) in a COVID-19-affected period (March 8, 2020 to Nov 30, 2020, n = 67) an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 29 publications
0
15
1
Order By: Relevance
“…The COVID-19 pandemic and related restrictions have resulted in severe limitations in neonatal care provision, 18 especially regarding acknowledged elements of IFCDC. 15 21–27 The frequently implemented separation of parents and their newborns has negative implications for the health outcomes of newborns, 28–30 interfering with acknowledged practices such as KMC, skin-to-skin contact 31 and breast feeding. 32 The reduction of parental presence in the neonatal intensive care units (NICU) has led to increased stress and mental health problems among parents and families, raising the risk of postnatal depression and post-traumatic stress syndrome and limited opportunities for parent–infant bonding, 14 15 while staff shortages and the lack of available guidelines have led to high levels of stress and anxiety among health professionals.…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic and related restrictions have resulted in severe limitations in neonatal care provision, 18 especially regarding acknowledged elements of IFCDC. 15 21–27 The frequently implemented separation of parents and their newborns has negative implications for the health outcomes of newborns, 28–30 interfering with acknowledged practices such as KMC, skin-to-skin contact 31 and breast feeding. 32 The reduction of parental presence in the neonatal intensive care units (NICU) has led to increased stress and mental health problems among parents and families, raising the risk of postnatal depression and post-traumatic stress syndrome and limited opportunities for parent–infant bonding, 14 15 while staff shortages and the lack of available guidelines have led to high levels of stress and anxiety among health professionals.…”
Section: Introductionmentioning
confidence: 99%
“…For example, during the COVID-19 pandemic, Neonatal Intensive Care Unit policies commonly restricted visiting to a single person for a limited period per day ( 135 ). Visiting policies that referred to “parents”, and did not differentiate between fathers and mothers or prioritize mothers, resulted in increased mother-infant separation with an associated adverse impact on breastfeeding and the mother-infant relationship ( 135 , 136 ).…”
Section: What Are the Consequences Of These Language Changes?mentioning
confidence: 99%
“…New “parents” do not have the same health needs or experiences as new “mothers” although language in publications or research design that does not distinguish between these groups can suggest that they do [e.g. ( 136 )]. Research on women's health or maternal and child health that is de-sexed may be more difficult to find as search terms disappear and so result in it being overlooked in indexing for initiatives such as the United Nations Sustainable Development Goals ( 142 ).…”
Section: What Are the Consequences Of These Language Changes?mentioning
confidence: 99%
“…Family presence at bedside is vital for family engagement, parent-infant attachment, shared decisionmaking/family-team communication, and medical care and discharge readiness for the infant. (Scala et al, 2021). Furthermore, as disparities in ability to be present at bedside have existed even prior to the pandemic, they have become more pronounced and exacerbated during the pandemic (Pang et al, 2021).…”
Section: Reduced Visitationmentioning
confidence: 99%
“…During COVID‐19, these challenges were exacerbated with an increase in financial difficulties, schools and childcare settings closing for in‐person services, and reduced availability of resources (e.g., ability for parents and siblings to stay in Ronald McDonald house). Practitioners from one US hospital reported that in comparison to the same period a year before, during March through May 2020, families visited less frequently (47% of days in comparison to 97% the year before) and infants received less frequent developmental care activities and for a shorter duration from both families and staff (Scala et al., 2021 ). Furthermore, as disparities in ability to be present at bedside have existed even prior to the pandemic, they have become more pronounced and exacerbated during the pandemic (Pang et al., 2021 ).…”
Section: Covid‐19 and The Nicu Environmentmentioning
confidence: 99%